Perancangan E-Commerce Pada Kerupuk 207 Jambi Berbasis Web - Tamara Dewi, Bella; Haris, Abdul; Feranika, Ayu (LPPM STIKOM Dinamika Bangsa, 2023)
Kerupuk 207 Jambi is one of the company that moving at selling product where the processes of promotion and sales still use manual way. So that problems occur is difficulty of increasing sales earnings with a big amount, a lack of facilities promotion which may be done by low cost , and a lack of facilities the provision of information the product offered. This research aims to design of system e-commerce And this research using the PHP programming language, DBMS MySQL, and waterfall for development system method. This research has stages such as identification problems, study of literature, gathering data, design system, development system, and making final reports. The result of this research is that this system is ease Kerupuk 207 Jambi in promoting with low cost, expanding the territory promotion and sales that can be inflated without having to awaiting customers come to the place